Tricking locusts into staying at home - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
Scientists at the International Centre of Insect Physiology and Ecology (ICIPE) in Kenya have decoded the locust's chemical language, and they can now stop them swarming. Kept in their home territories, the locusts become more vulnerable to attack...